Patients With Bicuspid Aortic Stenosis Demonstrate Adverse Left Ventricular Remodeling and Impaired Cardiac Function Before Surgery With Increased Risk of Postoperative Heart Failure. Issue 17 (16th August 2022) - Wedin, Johan O.; Vedin, Ola; Rodin, Sergey; Simonson, Oscar E.; Hörsne Malmborg, Jonathan; Pallin, Johan; James, Stefan K.; Flachskampf, Frank A.; Ståhle, Elisabeth; Grinnemo, Karl-Henrik
Abstract : Background: Differences in adverse cardiac remodeling between patients who have bicuspid (BAV) and tricuspid aortic valve (TAV) with severe isolated aortic stenosis (AS) and its prognostic impact after surgical aortic valve replacement remains unclear. We sought to investigate differences in preoperative diastolic and systolic function in patients with BAV and TAV who have severe isolated AS and the incidence of postoperative heart failure hospitalization and mortality. Methods: Two hundred seventy-one patients with BAV (n=152) or TAV (n=119) and severe isolated AS without coronary artery disease or other valvular heart disease, scheduled for surgical aortic valve replacement, were prospectively included. Comprehensive preoperative echocardiographic assessment of left ventricular (LV) diastolic and systolic function was performed. The heart failure events were registered during a mean prospective follow-up of 1260 days versus 1441 days for patients with BAV or TAV, respectively. Results: Patients with BAV had a more pronounced LV hypertrophy with significantly higher indexed LV mass ([LVMi] 134 g/m 2 versus 104 g/m 2, P <0.001), higher prevalence of LV diastolic dysfunction (72% versus 44%, P <0.001), reduced LV ejection fraction (55% versus 60%, P <0.001), significantly impaired global longitudinal strain ( P <0.001), significantly higher NT-proBNP (N-terminal pro-brain natriuretic peptide) levels ( P =0.007), and a higher prevalence of preoperative levosimendan treatment ( P <0.001) than patients with TAV. LVMi was associated with diastolic dysfunction in both patients with BAV and TAV. There was a significant interaction between aortic valve morphology and LVMi on LV ejection fraction, which indicated a pronounced association between LVMi and LV ejection fraction for patients with BAV and lack of association between LVMi and LV ejection fraction for patients with TAV. Postoperatively, the patients with BAV required significantly more inotropic support ( P <0.001). The patients with BAV had a higher cumulative incidence of postoperative heart failure admissions compared with patients with TAV (28.2% versus 10.6% at 6 years after aortic valve replacement, log-rank P =0.004). Survival was not different between patients with BAV and TAV (log-rank P =0.165). Conclusions: Although they were significantly younger, patients with BAV who had isolated severe AS had worse preoperative LV function and an increased risk of postoperative heart failure hospitalization compared with patients who had TAV. Our findings suggest that patients who have BAV with AS might benefit from closer surveillance and possibly earlier intervention.